The Influences of Competence and Motivation on Teacher Performance at Integrated Quran Primary School Nurul Islam Johar Karawang - Rahmawati, Dalfanida; Asep Jamaludin; Nandan; Amran Harun; Md Asrul Nasid Masrom (Research in Management of Technology and Business, 2024)
This paper aims to analyse the influences of competence and motivation on teacher performance. The competence variable comprises knowledge, understanding, abilities and skills, value, attitude and interest. Motivation consists of the need for achievement, expanded relationships, and power. This is an associative quantitative research, and a questionnaire was used to collect the data. The study’s sample is 52 teachers from the Basic School of the Integrated Quran Nurul Islam Johar using a saturated sampling technique when the sample size equals the population. The data was analysed by the use of multiple linear regression using SPSS 29 software. This study showed that competency significantly influences teacher performance, while surprisingly, motivation was insignificant. Therefore, the school management must emphasise training, managing human resources, and improving the quality of learning, which would eventually enhance performance.